Advertisement Remove all ads

Verify :- x^3 – y^3 = (x – y) (x^2 + xy + y^2) - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Verify :- x3 – y3 = (x – y) (x2 + xy + y2)

Advertisement Remove all ads

Solution

x3 – y3 (– y)(x2 xy2)

Wknothat,

(– y)3 x3 – y3 – 3xy(– y)

⇒ x3 − y3 (– y)3 3xy(– y)

⇒ x3 − y3 (– y)[(– y)2 3xy]                              Takin(x - y)common

⇒ x3 − y3 (– y)[(x2 y2 – 2xy3xy]

⇒ x3 y3 (– y)(x2 y2 xy)

Concept: Algebraic Identities
  Is there an error in this question or solution?

APPEARS IN

NCERT Class 9 Maths
Chapter 2 Polynomials
Exercise 2.5 | Q 9.2 | Page 49

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×